Mentoring Activities Results and Preferences in Secondary and Higher Vocational Education Students‟ Choice - Repina, Olga K. (International Journal of Psychosocial Rehabilitation, 2020)
The relevance of the problem under consideration is due to, on the one hand, the need to restore mentoring system as an effective form of staff development, and, on the other hand, lack of mechanisms and tools for implementing mentoring. One of the main aspects of mentoring practice is to determine effective results of mentoring activities, and there is no clear understanding in this matter. The article reveals the outcome of studying mentors’ existing views on mentoring activities results and expectations (preferences) of secondary and higher vocational education students’ interaction results with mentors. The leading research method of studying this problem is to analyze activity products, namely, completed mentors’ diaries. This analysis makes it possible to reveal mentoring activities results that are significant for mentors. An additional research method is survey among higher and secondary vocational education students so as to find out their preferences in selecting various results. The outcome of the study presented in the article is the typology of mentoring practice results. Thanks to survey among 30 students of secondary vocational education, aged 16-17 and 29 students of higher education at the age of 20-21, differences in their preferences of educational results from working with mentors were revealed. The materials of the article are of practical value for constructing a model for assessing mentoring practice effectiveness, for educational organizations managers’ planning the areas of joint work of mentors and mentees.